Locked in Time Animal Behavior Unearthed in 50 Extraordinary Fossils - Lomax, Dean R.; Nicholls, Robert (Columbia University Press, 2021)
Fossils allow us to picture the forms of life that inhabited the earth eons ago. But we long to know more: how did these animals actually behave? We are fascinated by the daily lives of our fellow creatures-how they reproduce and raise their young, how they hunt their prey or elude their predators, and more. What would it be like to see prehistoric animals as they lived and breathed?From dinosaurs fighting to their deaths to elephant-sized burrowing ground sloths, this book takes readers on a global journey deep into the earth's past. Locked in Time showcases fifty of the most astonishing fossils ever found, brought together in five fascinating chapters that offer an unprecedented glimpse at the real-life behaviors of prehistoric animals. Dean R. Lomax examines the extraordinary direct evidence of fossils captured in the midst of everyday action, such as dinosaurs sitting on their eggs like birds, Jurassic flies preserved while mating, a T. rex infected by parasites. Each fossil, he reveals, tells a unique story about prehistoric life. Many recall behaviors typical of animals familiar to us today, evoking the chain of evolution that links all living things to their distant ancestors. Locked in Time allows us to see that fossils are not just inanimate objects: they can record the life stories of creatures as fully alive as any today. Striking and scientifically rigorous illustrations by renowned paleoartist Bob Nicholls bring these breathtaking moments to life